Pelatihan Pengujian Beton Bagi Laboran Teknik Sipil Di Kota Pekanbaru - Alfian Saleh; Muthia Anggraini; Virgo Trisep Haris (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2021)
Abstract: A laboratory assistant is someone who has expertise and works in a laboratory and helps student learning processes (practicum) and lecturer research. In addition to laboratory laboratory assistants are also assisted by assisting the work of the laboratory. Given the importance of the role of a concrete laboratory assistant in supporting practical activities or testing in the laboratory, it is very important to improve the abilities and competencies of a concrete laboratory worker. These competencies need to be prepared considering technological advances, scientific developments continue to develop so that the roles and insights possessed by concrete laboratory workers are needed to answer all these challenges. In overcoming partner problems, the service team provides solutions in the form of concrete testing training for laboratory workers. The steps for implementing the solutions offered in overcoming these problems are four stages, namely (1) the planning stage, (2) the implementation stage, and (3) the evaluation stage. From the results obtained, there is an increase in the results of 62.1% of the preetest and posttest questions. Then 80% of the participants got a good score and 20% of the participants got a pretty good score.            Keywords: Laboratory Asistant, Concrete TestingAbstrak: Laboran adalah seseorang yang memiliki keahlian dan bekerja di laboratorium serta membantu proses pembelajaran mahasiswa (praktikum) dan penelitian dosen. Selain laboran laboratorium juga dibantu oleh asisten yang membantu pekerjaan dari laboratorium. Mengingat pentingnya peran seorang laboran beton dalam menunjang aktifitas praktikum ataupun pengujian di laboratorium, maka kemampuan dan kompetensi yang dimiliki seorang tenaga laboran beton sangat penting untuk ditingkatkan. Kompetensi ini perlu dipersiapkan mengingat kemajuan teknologi, perkembangan ilmu pengetahuan terus berkembang sehingga peran dan wawasan yang dimiliki oleh laboran beton sangat dibutuhkan untuk menjawab semua tantangan tersebut. Dalam mengatasi permasalahan mitra maka tim pengabdian memberikan solusi berupa pelatihan pengujian beton bagi laboran. Langkah-langkah pelaksanaan solusi yang ditawarkan dalam mengatasi permasalahan tersebut yaitu ada empat tahap yaitu (1) tahap perencanaan, (2) tahap pelaksanaan, (3) tahap evaluasi. Dari hasil yang didapat terdapat peningkatan hasil sebesar 62,1% dari soal preetest dan posttest. Kemudian sebesar 80% peserta mendapatkan nilai baik dan 20% peserta mendapatkan nilai cukup baik.Kata Kunci: Laboran, Pengujian Beton